Uma análise do desenvolvimento histórico da educação teológica indígena no Protestantismo brasileiro - Oliveira, Paulo (Vox Scripturae - Revista Teológica Internacional, 2011)
The present article, this thesis presents the history of approximately three decades concerning two Biblical Institutes and one Bible Training Center. Respectively, the Biblical Institute Reverend Felipe Landes and Cades Barneia located in the state of Mato Grosso do Sul in the cities of Dourados and Aquidauana, and the Ami Training Center in the state of Mato Grosso located in the Guimarães Plateau. These institutions aim at preparing evangelical indigenous leaders, and have indigenous leaders and docents. The history presented in this research begins in 1978. The path followed by these schools is the same as the one followed by our Seminars and Theological Colleges in Brazil, which aim at non-indigenous people. This paper presents the main components of these theological institutions, systematizing a series of information related to this aspect. This research also analyses the institution’s main components, such as, goals, curriculums and docent body, raising questions pertinent to each of these topics. To conclude, the paper gives five suggestions divided into steps, to make it more practical, for the search of a relevant theological education. The need for further studies, which include other aspects not developed here, is recognized.
Keywords: Theological training for indigenous leaders; theological curriculum